The Power and Peril of “Vulnerability”: Approaching Community Labels with Caution in Climate Change Research - Haalboom, Bethany; Natcher, David C. (ARCTIC, 2012)
Indigenous communities in the Arctic have become increasingly characterized as “vulnerable” in the context of climate change research. We question the use and application of this term in light of the potential consequences it may bring for indigenous peoples. First, the label “vulnerable” is often generated by those who are more or less unfamiliar with the complexities of local culture, economies, and capabilities. Second, we are concerned that such labels can generate misguided actions and policy responses built on how peoples and places come to be seen and understood by others. Third, the label “vulnerable” has the potential to shape how northern indigenous peoples come to see themselves as they construct their own identities—and identifying themselves as vulnerable may ultimately hinder their efforts to gain greater autonomy over their own affairs. As researchers become more engaged in the social dimensions of climate-change research, we encourage more careful and critical attention to the power and potential peril of community labels. Les communautés indigènes de l’Arctique sont de plus en plus souvent caractérisées de « vulnérables » dans le contexte de la recherche sur le changement climatique. Nous mettons en doute l’utilisation et l’application de ce terme à la lumière des conséquences éventuelles qu’il risque d’apporter aux peuples indigènes. Premièrement, l’étiquette « vulnérable » est souvent apposée par des personnes qui sont plus ou moins au courant des complexités de la culture, des économies et des capacités locales. Deuxièmement, nous nous inquiétons du fait que ces étiquettes peuvent se traduire par des mesures malavisées de même que par des politiques qui tiennent compte de la manière dont les peuples et les lieux sont perçus et compris par les autres. Troisièmement, l’étiquette « vulnérable » a la possibilité de déterminer la façon dont les peuples indigènes du Nord se voient quand vient le temps de définir leur propre identité, sans compter que le fait de s’identifier comme vulnérables ...